The Influence of Ethical Considerations and Locus of Control on Managers' Evaluation Judgments at The Adverse Selection Condition - Susanti, Vivi Ani (Jurnal Widya Manajemen & Akuntansi, 2003)
This research aimed at investigating the influence of ethical consideration and locus of control, constituting a personality variable, on the policies made by a manager to continue or discontinue a project that is not profitable due to private information and incentive to shirk (adverse selection) The agency theory views personal interest as the only basis to make economic decisions related to continuing or discontinuing a project that is not profitable based on incentives received by a manager. Whereas, the ethics based on the cognitive moral development views that a manager as a decision maker will consider ethics as an economic behavior constraint for the decision maker. At the same time, the internal and external locus of control will influence the persona capability of a manager to be a self-confident or luck, fate or destiny factor dependent in relation to the quality of decision being made. Data analysis using multiple regression and ANOVA showed that locus of control moderates the relationship between ethics and manager policies in decision making to continue or discontinue a project that is not profitable during the condition of adverse selection. The findings implied that ethics and locus of control explicitly influence the decision making by a manager during the condition of adverse selection.